2023
DOI: 10.5812/ijpr-136131
|View full text |Cite
|
Sign up to set email alerts
|

Co-treatment of Naringenin and Ketoprofen-RGD Suppresses Cell Proliferation via Calmodulin/PDE/cAMP/PKA Axis Pathway in Leukemia and Ovarian Cancer Cells

Abstract: Background: Naringenin (Nar) has anti-inflammatory and anticarcinogenic properties. Arginine-glycine- aspartate (RGD) is a tripeptidic sequence used as an integrin ligand and targeting system for delivering chemotherapeutic agents to cancer cells. Objectives: In this study, the inhibitory effects of Nar and ketoprofen-RGD on leukemia and ovarian cancer cells (K562 and SKOV3) were explored for the first time, focusing on their proliferation activity and their anti-inflammatory capacity. Methods: Analyses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…It has been identified that SCL negatively regulates the STAT3 and AKT pathways and subsequently induces apoptosis in a variety of cancer cells (Afshari et al, 2020;Pan et al, 2020). However, previous studies have not explored the upstream mechanisms by which SCL influences these pathways.…”
Section: Scl Promotes the Sumoylation Of Vegfr2 And Retained It In Th...mentioning
confidence: 99%
“…It has been identified that SCL negatively regulates the STAT3 and AKT pathways and subsequently induces apoptosis in a variety of cancer cells (Afshari et al, 2020;Pan et al, 2020). However, previous studies have not explored the upstream mechanisms by which SCL influences these pathways.…”
Section: Scl Promotes the Sumoylation Of Vegfr2 And Retained It In Th...mentioning
confidence: 99%